LOW DOSE RATE BRACHYTHERAPY CAESIUM-137 AFTERLOADING IN THE TREATMENT OF CARCINOMA OF UTERINE CERVIX IN SRINAGARIND HOSPITAL: ANALYSIS OF ACTURIAL SURVIVAL RATE - PESEE, Montien; TANGVORAPHONKCHAI, Vorachai; REAMSIRI, Tweesak; KIRDPON, Wichit; TUNGSUBUTRA, Kawee; KHWAKONG, Kuakoon; NGAMNASEOW, Naowarat (The ASEAN Journal of Radiology, 2023)
From October 1982 to December 1985, 412 patients with invasive uterine cervical carcinoma were treated with radiotherapy alone at the Division of Radiotherapy, Department of Radiology, Faculty of lledicine, Khon Kaen University, Khon Kaen, Thailand. The patients were in stages IB, IIA, IIB, IIIA, IIIB, IVA and IVB with 13, 5, 176, 5, 164, 14 and 15 cases respectively. Treatment methods were external irradiation 5000 cGy in 5 weeks in addition to intracavitary low dose rate brachytherapy 5400 mghr once or 3600 mghr twice after external radiotherapy. 66.4% of patients received brachytherapy after teletherapy more than 2 week interval. The average point A dose was 89.63 Gy and point B dose was 61.59 Gy. The acturial 3 year survival rates for stage IB, IIA, IIB, IIIA, IIIB, IVA and IVB were 89%, 100%, 70%, 60%, 56%, 28%, and 29% respectively. The 5 year acturial survival rates for stage IIB and IIIB which represent the highest number of the populations in this study were 63% and 39% respectively. The 5 year acturial survival rates for small size tumor less than 2 cm in diameter and tumor size larger than 2 cm in diameter were 74% and 56% respectively. Our study had been reported previously about residual tumors and complications.